Internet news about Ukraine and the “audience agenda”: topics, sources and the audience aggressiveness - Rožukalne, Anda (Žurnalistikos tyrimai, 2015)
Euromaidan in Kiev, the annexation of Crimea and the war in Eastern Ukraine had become the most important international events that impacted media content in 2013 and 2014. This paper provides research that intends to analyse the interrelation between news content of the three largest news sites in Latvia (Delfi.lv, Apollo.lv, Tvnet.lv) and the Latvian and Russian-speaking audience reaction to the news about the events in Ukraine in 2014. By using a unique tool for audience behaviour analysis “The Index of Internet Aggressiveness” in this research, the level of audience aggressiveness that appears within audience comments has been analysed with the aim to find out how and if the professional approach of the news producers influences the aggressiveness of the news site’s audience. The three different groups of data from the Index of Internet Aggressiveness are used to measure audience behaviour: the quantity of aggressive keywords used in the comments by audience members that create a significant rise in the Index of Internet Aggressiveness next to the news on Ukraine; content analysis of the most aggressively commented news articles about the events in Ukraine; the semi-structured qualitative interviews with editors of news sites that explain professional routines. The most significant conclusions of the research show the domination of the official Russian media outlets among the news sources about Ukraine. By republishing ready-made and easily accessible news stories, independent news sites of Latvia have become distributors and multiplicators of messages favourable to the Russian version of the events in Ukraine.